Fractured Atmospherics - Boswell, Anna (Interstices: Journal of Architecture and Related Arts, 2014)
Mobilising Jacques Rancière’s concept of the “distribution of the sensible” and Sara Ahmed’s notion of “angles of arrival”, this paper considers design work implicit in the settler-colonial enterprise and incompatible structures of affect that may be said to underwrite a settler-colonial place. It is interested in the atmospherics of fracture itself, and in the question of the translatability of affect and atmosphere to Indigenous worlds. What might it mean to conceive of a place as possessing the capacity to respond to human intervention in affective terms, it asks, and who or what might be ‘moved’ as a result?